Use of complementary and alternative medicine and folk medicine in Medellín, 2005 - Luz Stella Alvarez C (Universidad de Antioquia, 2007)
Objective: to explore health resources chosen by Medellín's residents when they feel ill and the reasons why they decide to use Colombian folk medicine and Complementary and Alternative Medicine resources. Methods: this research was based on the premises shared by the majority of the qualitative methods, and specially by two methodologies: the Grounded Theory (GT) and Rapid Assessment Process (RAP). Forty-six people from various social classes, who were afﬁliated with different health insurance companies as well as uninsured were interviewed. Interviews were carried out from July to September 2005. Results: the study found that many people, especially those with low or very low income seek Colombian folk medicine practices resources when they feel sick. These practices and their practitioners have taken new names to adapt themselves to new tendencies in medicine but they actually keep the traditional characteristics of Colombian folk medicine. Complementary and alternative medicine therapies such as acupuncture, homeopathy, and bioenergetics exercised by physicians licensed from certiﬁed universities are sought mostly by middle and upper class people, especially by those with a high educational level. These patients have in common that they feel discomfort with the biologist emphasis of Western medicine so they seek an integral treatment integrating body, mind, and spirit.